PTU-039 Anaemia – should all patients have radiological investigations?. (17th June 2017) - Mirza, N; Elgizoli, B; Williams, G; Mir, MH; Tan, C; Khalid, S
Abstract : Introduction: BSG guideline for anaemia does not recommended use of routine radiological investigations to rule out non gastrointestinal malignancies. It advocates the use of radiological testing to rule out GI cancer only, if patient is not suitable to have endoscopy. We audited the data of patients who were referred for endoscopic investigations for anaemia. We aimed to identify whether there is any role of routine imaging in these patients and how likely are we to miss GI cancers when patients are not suitable to have endoscopic investigations. Method: We analysed data retrospectively for patients who underwent endoscopic investigations for Anaemia over a six month period in 2015. Further data was collected through pathology and radiology reporting system until July 2016 to analyse the yield of radiological imaging. 335 patients had bidirectional endoscopic investigations and 52 patients under the age of 50 and 56 patients with no radiological investigations were excluded. Results: 227 patients above the age 50 were included who had both endoscopy and radiological investigations. We found ratio of 2:1 of GI malignancy to non GI malignancy. A total of 11 malignancies were found with 7 colorectal and 4 extra gastrointestinal cancers including 1 pancreatic, 1 adrenal and 2 renal. 1 patient with renal malignancy also had stomach ulcer as a possible cause of anaemia. No GI malignancy was missed on radiological investigations and we found virtual endoscopy as good as endoscopic examination for diagnostic evaluation. Gastroscopies did not identify any cancer and unless patient is symptomatic it may have low yield in this group of patients Conclusion: We found high yield of non GI malignancies in our cohort and suggest that all patients should have radiological investigations. No cancers were missed on CT imaging and it is reasonable to employ this in line with BSG guidelines, when patient is not suitable to have endoscopic investigations. Disclosure of Interest: None Declared